THE EXAMINATION OF FACTORS AFFECTING CUSTOMER SATISFACTION IN MOBILE BANKING - Dinda Ramadhanty, Savina
Supported by the technological advances these days, technology has enabled us to use financial services more efficiently. However, this will not happen without going through several processes, one of which changes the customer's behavior. These changes are the way people carry out common transactions, specifically beginning to use mobile banking. To equalize perception, mobile banking is various banking activities that the customer can conduct through their mobile devices. Many studies, have focused more on the behavioral intention that influenced people to adopt mobile banking. However, this study focuses on post-adoption behavior, such as customer satisfaction. Thus, in this study, we examine the relationship between trust and customer satisfaction and trust as the mediating variable on the relationship of system quality, information quality, service quality, task characteristics, and structural assurance on customer satisfaction. This study is conducted in Indonesia and collected data through an online questionnaire. The respondents must be above 17 years old and have used mobile banking. The data used in this study was analyzed by using PLS-SEM. According to the results, trust has a significant relationship to customer satisfaction. Moreover, in the relationship between information quality, task characteristics, and structural assurance with customer satisfaction, trust plays a crucial role as a full mediator. Meanwhile, trust act as a partial mediator in the relationship between system quality and service quality. Therefore, banks that are considered trustworthy by their customers usually have satisfactory mobile banking. Thus, this study suggests that banks should first provide reliable, sufficient, up-to-date, and appropriate information to the customers to improve customer satisfaction by trust. Second, banks should ensure the customers that their mobile banking is safe to use, protect them against any payment problems, and be in a secure environment. Finally, banks should also provide dependable, prompt, professional, and personalized service while also provide convenient and easy to use access to the customers.